How much is enough? Approaches to public participation in shale gas regulation across England, France, and Algeria - Aczel,M; Makuch,K; Chibane,M (The Extractive Industries and Society, 2018)
We examine ‘fracking’ for shale gas extraction in England, France, and Algeria, framed from the perspective of level of acceptance by communities and general public. We explore the extent to which public participation in decision-making should play a role in fracking regulation, and evaluate whether the level of public participation matches the legal requirements. Our position on the adequacy of fracking regulation is from the perspective of the public dissenter, outlining a legal and normative basis for public participation in decision-making on fracking. We highlight relevant laws and policies to understand and evaluate adequacy of relevant regulatory processes.We offer strong yet nuanced argumentation, creating space for further discussion by academics, the public, regulators, local decision-makers, fracking companies and others. This is not a typical social-psychology, legal, sociology, or human geography research paper, as we take a position from the beginning: that the public ought to be involved in decisions related to the regulation of fracking, and argue that we validate our approach by supporting our claims throughout the work.